E-Cigarette/Vape-Associated Lung Injury as a Cause of Interstitial Lung Disease - Sana Ullah; Khan Afrid, Muhammad Asif (Indus Journal of Bioscience Research, 2025)
Background: The increasing prevalence of e-cigarette and vaping product use has introduced new pulmonary risks, including e-cigarette or vaping-associated lung injury (EVALI). Initially recognized as an acute lung injury, EVALI has raised concern due to emerging evidence of long-term respiratory complications, particularly interstitial lung disease (ILD). Despite various case reports, the exact relationship between vaping and ILD remains underexplored in clinical cohorts. Objective: To investigate the association between EVALI and the development of ILD, examining clinical features, radiological patterns, and histopathological findings among patients presenting with recent vaping exposure. Methods: This prospective observational study was conducted from 8 January to 8 April 2025 at Hayatabad Medical Complex Peshawar, Pakistan. Patients with respiratory symptoms and a history of vaping within the preceding 90 days were enrolled. Diagnostic assessments included high-resolution computed tomography (HRCT), pulmonary function tests (PFTs), and lung biopsies when indicated. Data were analyzed for demographic trends, vaping exposure characteristics, and lung injury patterns. Results: Of the 60 patients included, 45 (75%) showed HRCT findings suggestive of ILD, predominantly organizing pneumonia (OP) and diffuse alveolar damage (DAD). Histopathological analysis in 15 cases confirmed interstitial inflammation with early fibrotic changes. Most patients (80%) with ILD patterns reported the use of THC-containing vaping products. A statistically significant association (p<0.05) was found between THC exposure and ILD development. Conclusion: Our findings support a compelling link between vaping—particularly products containing THC—and the development of interstitial lung disease. Enhanced surveillance, public awareness, and stricter product regulation are crucial to mitigate these emerging pulmonary risks.